AL-‘UQŪD AL-MURAKKABAH SEBAGAI PROGRESIFITAS MAQĀŞID ASY-SYARĪ’AH DALAM SISTEM EKONOMI ISLAM - Mawardi Mawardi (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
Al-â€˜UqÅ«d al-murakkabah is a contract development method which is currently practiced in almost all sharia financial institutions, banks or non-banks. Normatively, the development of al-â€˜uqÅ«d al-murakkabah has several methods that must establish their ability in sharia. However, normatively, there are many rules that must always be written as part of normative references. In this paper, al-'uqÅ«d-murakkabah is analyzed from the perspective of progressif of maqÄsid asy-syarÄ«'ah, with the hope that it can be found the meeting point between sharia objectives and economic goals through the al-'uqu method al- murakkabah